Win-win ecology : how the earth's species can survive in the midst of human enterprise - Rosenzweig, Michael L. (Oxford University Press, 2003)
"In this book, ecologist Michael Rosenzweig finds that ecological science actually rejects such polarization. Instead it suggests that, to be successful, conservation must discover how we can blend a rich natural world into the world of economic activity. This revolutionary common ground between development and conservation is called reconciliation ecology: creating and maintaining species-friendly habitats in the very places where people live, work, or play."--Jacket